Swearing and gender dynamics in urban Surabaya: Understanding Gen Z’s swearing in Surabaya’s arek culture - Sholihatin, Endang; Haryono, Nanang (Jurnal Sosiologi Dialektika, 2024)
Swearing in society is a multifaceted phenomenon influenced. The purpose of this research is to understand the context of swearing among Generation Z in Surabaya and the differences in swearing between male and female Gen Z individuals in Surabaya. This research uses qualitative research methods involving 45 Generation Z informants from Surabaya. The results of the research show that the decision by Gen Z Surabaya is influenced by emotional context, social norms, culture, and group bonding to strengthen social ties, express emotions, and maintain their unique identity. Male Gen Z in Surabaya use the swear word “jancuk” with a higher pitch and rarely modify it, while female Gen Z use it with a lower pitch and frequently modify it. The conclusions of this research are first, the context of swearing among Generation Z in Surabaya occurs in informal situations among close friends for joking, easing the atmosphere, and insulting to demean the conversation partner, all influenced by Arek culture. Secondly, the difference in swearing between male and female Gen Z in Surabaya is that male Gen Z often use a higher pitch and rarely use modified swear words, while female Gen Z do not always use a high pitch and often use modified swear words to maintain their image. The use of swearing by both male and female Gen Z within the Arek Surabaya culture demonstrates intimacy, openness, egalitarianism, and the absence of social distance.